tInjauan YURIDIS ATAS PERATURAN DAERAH Provinsi kalimantan timur Nomor 1 Tahun 2015 tentang PEDOMAN PENGAKUAN DAN PERLINDUNGAN MASYARAKAT HUKUM ADAT DI PROVINSI KALIMANTAN TIMUR - Komela Avan (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
AbstrcakThe thesis entitled Juridical Review of Local Regulations of East Kalimantan Province No. 1/2015 on the Guidelines for Recognition and Protection of Indigenous People’s Community in East Kalimantan Province, is written to answer two following problem formulation: 1) Based on synchronicity of legislation, can this Local Regulation of East Kalimantan Province be taken as juridical basis for recognition and protection of Indigenous People’s Community of East Kalimantan?; 2) Can this local regulation be applied effectively as juridical basis for providing recognition and protection for indigenous people’s community in East Kalimantan?In writing the thesis, the writer conducted a normative juridical review of the Local Regulation of East Kalimantan Province No. 1/2015 on the Guidelines for Recognition and Protection of Indigenous People in East Kalimantan Province by collecting law material in the forms of legislations, local regulations and also theory on indigenous people’s community, on custom law that is relevant in doing study on this local regulation, through library research method.This thesis consists of 4 (four) chapters and it is written in the following systematic composition:Chapter I is the Introduction containing the reasons of selecting the title and background of the writing, limitations of the issues discussed, purpose and object of the writing and expected benefits of the writing and also the research method used.Chapter II contains theoretical framework which covers four main points; Firstly, Indigenous People’s community; Secondly, the Adat Law; Thirdly, the Traditional Rights of Indigenous People over the Land, and; Fourthly, Local Regulations in Theory of Legislation.Chapter III is an analysis of the Local Regulations of East Kalimantan Province itself in the form of juridical review of two matters. First, the writer elaborated synchronicity of the Government Regulation of East Kalimantan Province No. 1/2015 in the configuration of related legislation’s codes of law on that same matter. Second, the writer made a review on the effectiveness of the government regulation as juridical instrument for Recognition and protection of Indigenous People’s community in East Kalimantan.Chapter IV contains the conclusions and recommendations after doing juridical review of the Local Regulation of East Kalimantan Province No. 1/ 2015.Keywords: Recognition and Protection of Indigenous People’s Community in East Kalimantan.